The Potential Use of Anticancer Peptides (ACPs) in the Treatment of Hepatocellular Carcinoma - Ng, Chu X.; Lee, Sau Har (Current Cancer Drug Targets, 2020)
Peptides have acquired increasing interest as promising therapeutics, particularly as anticancer alternatives during recent years. They have been reported to demonstrate incredible anticancer potentials due to their low manufacturing cost, ease of synthesis and great specificity and selectivity. Hepatocellular carcinoma (HCC) is among the leading cause of cancer death globally, and the effectiveness of current liver treatment has turned out to be a critical issue in treating the disease efficiently. Hence, new interventions are being explored for the treatment of hepatocellular carcinoma. Anticancer peptides (ACPs) were first identified as part of the innate immune system of living organisms, demonstrating promising activity against infectious diseases. Differentiated beyond the traditional effort on endogenous human peptides, the discovery of peptide drugs has evolved to rely more on isolation from other natural sources or through the medicinal chemistry approach. Up to the present time, the pharmaceutical industry intends to conduct more clinical trials for the development of peptides as alternative therapy since peptides possess numerous advantages such as high selectivity and efficacy against cancers over normal tissues, as well as a broad spectrum of anticancer activity. In this review, we present an overview of the literature concerning peptide’s physicochemical properties and describe the contemporary status of several anticancer peptides currently engaged in clinical trials for the treatment of hepatocellular carcinoma.
Keywords: liver cancer